(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to analyze and evaluate the sustainability of public debt in Libya and its relationship to economic growth during the period 2000–2023. The study employed a descriptive-analytical approach with an econometric component, utilizing the Vector Error Correction Model (VECM) to examine the dynamic relationship between the public debt-to-GDP ratio (dependent variable) and each of the following: economic growth rate, government spending, oil prices, and exchange rate (independent variables). The results of the modified Dickey-Fuller test (ADF) showed that all the study variables were first-order complementary (1). Furthermore, the Johansen test confirmed the existence of a long-term equilibrium relationship (co-integration) among the studied variables, with a Trace value of 79.68980, which is greater than the critical value at a significance level of 5%. The standard results for estimating the Vector Error Correction Model (VECM) demonstrated good explanatory power, with coefficients of determination (R²) ranging from 0.64 to 0.79, and an overall significance level of 9.159250 according to the F-test. The study confirmed a structural and significant impact of oil price volatility and economic growth on the long-term sustainability of public debt. It recommended diversifying national income sources to reduce dependence on oil price fluctuations and adopting prudent fiscal policies aimed at controlling current spending and activating the role of development spending to ensure the state’s ability to meet its financial obligations without compromising the rights of future generations.